Effects of the 4 week plyometric training program on explosive strength and agility for basketball players - Artan Kryeziu; Bujar Begu; Isa Asllani; Astrit Iseni (Turkish Journal of Kinesiology, 2019)
The paper was effects of the 4 week plyometric training program on explosive strength and agility for basketball players. Totally 20 basketball players were volunteered for the study (age = 15 years +/- 6 months). They were divided to 2 groups: the control group (CG, n = 10; height = 171.930 cm, weight = 70.840 kg, BMI = 20.563), the experimental-plyometric group (EG, n = 10; height = 173.090 cm, weight = 64.300 kg, BMI = 19.068). The tests are twelve (13) variables of them, 3 from anthropometric and 10 motor tests. According to the results of the CG, significant small differences are presented in two tests, such as 20m running (sprint) testing with significant differences (p= 0.013), and abdominal muscle testing with significant differences (p= 0.036). However, in the PG, significant differences in four tests, the jump from place to length with significant differences (p= 0.003), the high jump with the approach of one foot significant differences (p= 0.035), push-ups (pump) test with significant difference (p= 0.004), Illinois Agility test with significant difference (p= 0.004). Through which it was possible to conclude that the effects of the experimental-plyometric training program of the game basketball indicators.